Parenting Factors on Early Childhood Self-Confidence - Novela Rifa; Rakimahwati Rakimahwati (STAI Hubbulwathan Duri, 2023)
Developing children's self-confidence from an early age helps build rational thought processes, solve problems, increase achievement and performance levels and make good decisions in the future. This study aims to describe the parenting factors that trigger children's lack of confidence. This greatly impacts children's emotional and social development in their environment to provide several interventions to develop children's self-confidence. The subjects in the study of family factors on self-confidence in early childhood were two children in group B. The type of research used is a qualitative descriptive approach. Data collection using observation and interview techniques. Children who lack confidence may find it difficult to interact with other peers. The results showed that there are several factors of parenting patterns on children's self-confidence, such as authoritarian parenting, gender bias and parental knowledge. Parents and teachers play an important role in directing, motivating, and directing children to dare to perform in front of the class, talk to peers, and socialize with others. Then form interventions with play while learning that parents can do with children at home in order to develop children's self-confidence.